Correlates of institutionalization among the oldest old—Evidence from the multicenter AgeCoDe‐AgeQualiDe study. (2nd April 2021) - Hajek, André; Luppa, Melanie; Brettschneider, Christian; van der Leeden, Carolin; van den Bussche, Hendrik; Oey, Anke; Wiese, Birgitt; Weyerer, Siegfried; Werle, Jochen; Fuchs, Angela; Pentzek, Michael; Löbner, Margrit; et al.
Abstract: Objectives: There is a lack of studies identifying the correlates of institutionalization specifically among the oldest old. Therefore, our aim was to fill this gap in knowledge. Methods: Cross‐sectional data (Follow up wave 9; n  = 633 observations in the analytical sample) were used from the multicenter prospective cohort study "Needs, health service use, costs and health‐related quality of life in a large sample of oldest‐old primary care patients (85+)" Correlates of institutionalization among the oldest old—Evidence from a multicenter cohort study. The sample consists of primary care patients aged 86 years and over (mean 90.5 years, SD: 2.9 years). Sociodemographic and health‐related independent variables were included in our regression model. Institutionalization was defined as living in a nursing home or an old‐age home (not including assisted living facilities). Results: Out of the 633 participants, 502 individuals (79.3%) did not live in an institutionalized setting, whereas 73 individuals (20.7%) lived in an institutionalized setting. Multiple logistic regressions showed that the likelihood of institutionalization increased with being divorced/widowed/single (compared to being married; OR: 5.35 [95% CI: 1.75–16.36]), the presence of social isolation (OR: 2.07 [1.20–3.59]), more depressive symptoms (OR: 1.11 [1.01–1.23]), increased cognitive impairment (OR: 1.67 [1.31–2.15]) and higher levels of frailty (OR: 1.48 [1.07–2.06]). Conclusion: The study findings identified various sociodemographic and health‐related factors associated with institutionalization among the oldest old. Longitudinal studies are required to gain further insights into these associations. Key Points: Based on a large multicenter prospective cohort study, the aim was to examine the correlates of institutionalization among the oldest age group Institutionalization was associated with being divorced/widowed/single, social isolation, more depressive symptoms, increased cognitive impairment and frailty Study findings identified various sociodemographic and health‐related factors associated with institutionalization among the oldest old The implementation of flexible, tailored interventions addressing the specific circumstances of the caregiving situation to delay a transition or assure a well‐timed and well‐organized transition is required